Assessment of Carbon Stock in Community Forest (A Case Study from Barahi Community Forest) - Shrestha, Oshana; Magar, Lilu Kumari (Journal of Sustainability and Environmental Management, 2024)
Forests play a significant role in mitigating climate change by capturing carbon dioxide from the atmosphere and storing it in the form of biomass, deadwood, litter, and soils. Estimating the total carbon stock in any forest is crucial, as it provides both ecological and economic benefits through various environmental services. Given the recognised importance of community forests in mitigating the effects of climate change, and considering the scarcity of studies on carbon issues in the Nuwakot district, this research was conducted to determine the above- and below-ground carbon stocks in the Barahi community-managed forest, Nuwakot. The inventory of estimating above- and below-ground biomass of the forest was carried out using a stratified random sampling method. 17 plots were selected randomly. Forest biomass was calculated using standard allometric models. The below-ground biomass was estimated using a root-to-shoot ratio value of 1:5. The biomass stock density of a sampling plot was then converted to carbon stock densities after multiplication by the default carbon fraction of 0.47. The total above- and below-ground biomass was found to be 175.33 ± 18.75 t/ha and 34.38 ± 18.75 t/ha, respectively. The total forest carbon stock was found to be 98.57 ± 8.92 t/ha, with above-ground carbon stock 82.41 ± 8.92 t/ha and below-ground carbon stock 16.16 ± 8.92 t/ha, respectively. The study concluded that the studied CF has a high carbon sequestration potential and can serve as an important carbon sink contributing to climate change mitigation. Wise and sustainable management of the existing forest is highly recommended.